Large-Scale Atomistic Simulation of Sintering Process and Mechanical Properties of Al Matrix Composite with Different Reinforcements - Yongchao Zhu; Can Sui; Na Li; Lijuan Sun; Songtao Li (Metals)
Through molecular dynamics methods, composite models built with a large scale were employed to investigate the effects of different reinforcements, which were different from those used in most of the similar studies, where only a graphene nanosheet (GNS) or a rigid spherical particle was embedded in a metal matrix. Here, 27 GNSs or diamond particles were placed in the empty spaces between Al particles with random directions. Then, Al matrix composites were prepared by modeling a sintering process. Structural analysis and tensile modeling were carried out on the sintered composites. The results indicate that the density of the Al–graphene composite was higher and increased with growth in the size of the reinforcements, although the Al–graphene system required more heating time to achieve densification. Bigger GNSs were likely to increase the pore volume of the composite. Meanwhile, larger GNSs were also more beneficial for grain refinement, leading to growth in the ratio of Al atoms at grain boundaries. The greater impact of GNSs on the inner structure was not just derived from their high specific surface area, and this impact was enlarged if drawn as a function of the weight fraction rather than the surface area. However, tensile processes revealed that two-dimensional (2D) materials seemed to have no clear impact on the direct strengthening effect, and anisotropy could not be observed in the large-scale models. The biggest GNSs even led to reductions in both the tensile strength and ductility of the Al–graphene composite, which coincided with some experimental reports. The evolution of the inner structures indicated that GNSs have the same role as diamond particles in dislocation accumulation and crack propagation. The major advantage of GNSs is their ability to improve the densification and grain refinement of the metal matrix composite (MMC).